Serotyping and identification of predisposing factors for the occurrence and distribution of ovine pasteurellosis in Bonga sheep breed - Mengstie, Fisseha (Asian Journal of Medical and Biological Research, 2015)
Cross-sectional study for investigating the prevailing field serotypes and predisposing factors for the occurrence and distribution of ovine pasteurellosis in Bonga sheep breed of different agro-ecology of Adiyo (highland), Gawata (lowland) and Debub Bench (Midland) of Kaffa and Benchi Maji in southern Ethiopia was conducted during July 2012 to June 2013. For this purpose, a questioner survey to identify predisposing factors and laboratory analysis on samples to investigate the prevailing field serotypes were performed. In these regard, a total of 210 farmers were interviewed and 70 blood samples from each agro-ecology (total of 210) was randomly collected following standard procedures. Laboratory analysis was performed by indirect haemagglutination (IHA) technique at National Veterinary Institute (NVI), Debre Zeit, Ethiopia. The finding showed that, 34.8% of the farmers household main sources of income were dependent on sheep production in which ovine pasteurellosis had 81% of occurrence. Management of sheep like housing and sanitation of the barn were predisposing factors. Irrespective of agro-ecology, M. haemolytica A2 (52.4%) followed by A7 (42.4%) and A1 (31%) were detected where as P. multocida serotype was not detected. Among identified serotypes, highest prevalence of M. haemolytica A1 (37.1%) were detected in lowland where as A2 (62.9%) in Midland and lowland with equal prevalence and A7 (85.7%) in midland. Therefore, ovine pasteurellosis was the major disease of sheep identified with multiple losses in the production and M. haemolytica is the most common cause identified. Measures such as, improving management practices by providing optimal sanitation in housing, providing good quality supplement feeding during rainy season and minimizing stress factors should be taken into account to reduce the prevalence. In addition, the currently use vaccine (P. multocida biotype A) not incorporate the identified serotypes so that may not protect the disease. As a result, use of multivalent vaccine by incorporating those identified serotypes is necessary to effectively prevent the disease. Asian J. Med. Biol. Res. June 2015, 1(2): 175-181